Peran Penyuluh Pertanian Dalam Penerapan Teknologi Pertanian Ramah Lingkungan di Kecamatan Mojo Kabupaten Kediri - Risvita, Wuwun; Nadhirah, Aulia; Fibrianingtyas, Alya (Universitas Galuh, 2025)
The effectiveness of the eco-friendly farming technology is highly dependent on how farmers view and assess the role of extension workers. This study aims to analyze farmers' perceptions of agricultural extension workers in the application of eco-friendly farming technology. This study used a survey method from the results of interviews through questionnaires to 50 farmers in Mojo District. The results showed that the environmentally friendly agricultural technology was in the high category except for the role of extension workers as facilitators. The role of agricultural extension workers had an influence on the application of environmentally friendly agricultural technology by 47.7%. The role of extension workers as motivators and consultants partially had a positive effect. The role of extension workers as educators had a negative effect. This shows that the higher the intensity of extension and the increase in the application of environmentally friendly agricultural technology, the lower the farmers' trust in agricultural extension workers. The variables of the role of extension workers as catalysts, communicators and facilitators partially do not affect. The process of implementing the latest technology is influenced by several driving factors at the farmer level, including farmer characteristics, the nature of technology and competition between extension workers.